Organizational Renewal through Positive Management and Entrepreneurship - Zbierowski, Przemysław (Odnowa organizacyjna poprzez pozytywne zarządzanie i przedsiębiorczość, 2010)
The paper presents a combination of organizational entrepreneurship and positive organizational scholarship (POS) as a way of organizational renewal. Entrepreneurship has been considered a stimulus to renewal for some time, and POS is a new way of reaching the same objective. In the paper, we present the theory of positive organizational scholarship, which provides a new perspective for entrepreneurship. The key finding is the matrix of levels (individual, organizational and societal) and issues (causes, institutions and consequences) on the cross-section of POS and entrepreneurship. Finally, we outline the future research directions created by that cross-section.
Trwa pobieranie danych. Zaczekaj kilka sekund i spróbuj ponownie wyciąć lub skopiować obiekt., s. 76-89
Keywords: entrepreneurship; small business; positive studies